Organizational Staffing and Work AdjustmentOrganizational Staffing and Work Adjustment, by TzinerAharon. Westport CT: Praeger, 1990, 219 pp., $45.00, cloth. - Rothstein, Hannah (Academy of Management Review, 1992)
This article presents a review of the book ?Organizational Staffing and Work Adjustment,? by Aharon Tziner.